One-step fabrication of biodegradable superhydrophobic PLA fabric for continuous oil/water separation - Chen, Tianchi; Guo, Jie; Xu, Hao; Zhang, Jialu; Hu, Ningning; Liu, Hongtao (Applied surface science, 2022)
[Display omitted] •Superhydrophobic PLA surface can be prepared by a one-step spraying methods.•The as-prepared PLA fabric can be used for continuous oil-water separation.•The as-prepared PLA fabric can separate oil-water mixtures under harsh environments.•The as-prepared PLA fabric exhibits outstanding environmental and mechanical stability. Various types of functional materials incorporating superhydrophobic components have been rapidly developed for efficient oil/water separation. The post-processing of these used separated materials remains a challenging problem due to their non-biodegradable characteristics in natural environments, thus easily contributing to secondary contamination. Herein, we report a biodegradable superhydrophobic PLA fabric with hierarchical coral-like micro/nano structures by a one-step spraying method. The as-prepared PLA fabric was found to be both superhydrophobic and superoleophilic with a static water contact angle of 161 ± 2° and an oil contact angle of 0°. In addition, the as-prepared PLA nonwoven fabrics also revealed efficient continuous oil separation efficiency (>97.5%) and tiny water droplet collection efficiency, as well as high oil flux ranging from 2239 L·m−2·h−1 to 59,713 L·m−2·h−1. Furthermore, these fabrics retained their inherent wetting property and oil separation ability in a variety of acidic and basic solutions, 3.5 wt% NaCl solution, hot (100 °C), and freezing (0 °C) temperatures. This study provides a novel and environmentally friendly method for preparing biodegradable oil–water separation materials with green post-treatment characteristics when compared to the non-biodegradable separation materials, indicating potential applications in the fields of green water treatment and petroleum refining.